Unhealthy Alcohol Use Is Associated With Suboptimal Adherence to Isoniazid Preventive Therapy in Persons With HIV in Southwestern Uganda. (15th December 2022) - Muyindike, Winnie R.; Fatch, Robin; Cheng, Debbie M.; Emenyonu, Nneka I.; Forman, Leah; Ngabirano, Christine; Adong, Julian; Linas, Benjamin; Jacobson, Karen R.; Hahn, Judith A.
Abstract : Background: Unhealthy alcohol use is associated with increased progression to tuberculosis (TB) disease, but its effect on adherence to isoniazid (INH) preventive therapy is not known. Methods: This was a prospective study of persons with HIV with latent TB in southwestern Uganda reporting any current (previous 3 months) alcohol use or no alcohol consumption in the previous year (2:1 ratio). All received INH. We defined suboptimal adherence as <90% of days with at least 1 Medication Event Monitoring System cap opening, over the previous 90 days. Alcohol use was categorized as follows: none: no self-report and phosphatidylethanol (PEth) <8 ng/mL; moderate: Alcohol Use Disorders Identification Test-Consumption (AUDIT-C) 1–2 (women) or 1–3 (men) and/or PEth 8 ≥ 50 ng/mL; and unhealthy: AUDIT-C ≥3 (women) or ≥4 (men) and/or PEth ≥50 ng/mL. We used generalized estimating equation logistic regression analyses to assess the association between the level of alcohol use and suboptimal INH adherence. Results: Three hundred two persons were enrolled; 279 were on INH for 3 or more months. The prevalence of suboptimal INH adherence was 31.3% at 3 months and 43.9% at 6 months. The odds of suboptimal INH adherence were higher for unhealthy (adjusted odds ratio, 2.78; 95% confidence interval: 1.62 to 4.76) and moderate (adjusted odds ratio, 1.59; 95% confidence interval: 0.94 to 2.71) compared with no alcohol consumption. Conclusions: Suboptimal adherence to INH at 3 and 6 months was high among prospective study of persons with HIV and associated with unhealthy alcohol use. Adherence support and alcohol reduction strategies are needed for this group at high risk for active TB.